Hakikat Hak-hak Azazi Manusia dan Aktualisasinya di Indonesia - Suhadi, Suhadi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 1999)
The human rights are the fundamental, real universal basic rights possesed and adhered in every humankind. With his human rights, everybody can define and actualize the contens of his soul, doing his activities freely-in the limits of the fittingness and not distrubing other's human rights.Since the existence of human being the human rights are interesting issues for most of the people, because they are very essential. The United Nations Organization and the most countries in the world have acknolwedge, prevented, and implemented the human rights. Nevertheless, there are still many deviations, viotation, and acts of despising in the practice of the human rights, so that many people in the world including Indonesia are concerned with them.In Indonesia the human rights placed in the honoured place, having acknowledge and prevented. They are always encouraged to the implemented as best in the custom law and any other laws since empire, colonial, and pastcolonial eras. Yet, in their practice, they still facing many probelms.